Mapping The Role of Tax Agents in Auditing: A Bibliometric Analysis Using Vosviewer (1974-2025) - Nor Asiah Taib; Izlawanie Muhammad; Suhaila Abdul Hamid (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA